2020
DOI: 10.1101/2020.02.20.957746
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parallel CRISPR-Cas9 screens clarify impacts of p53 on screen performance

Abstract: 13CRISPR-Cas9 genome engineering has revolutionised high-throughput functional 14 genomic screens. However, recent work has raised concerns regarding the 15 performance of CRISPR-Cas9 screens using TP53 wild-type human cells due to a 16 p53-mediated DNA damage response (DDR) limiting the efficiency of generating 17 viable edited cells. To directly assess the impact of cellular p53 status on CRISPR-18Cas9 screen performance, we carried out parallel CRISPR-Cas9 screens in wild-type 19 and TP53 knockout human ret… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…Despite a computational method for the estimation of the gene-dependency level while taking account of the copy-number effect, it is experimentally demanding to determine copy numbers for cell types of interest, while it is still difficult to resolve mismatch-tolerance effect 11,16 . What's more, it has recently been reported that Cas9-induced DSBs posed obstacles to high-throughput screens in human non-transformed cells via p53-dependent cell growth arrest [17][18][19][20] . High-efficiency Cas9 editing could cause cell death in human pluripotent stem cells (hPSCs) 20 and G1 cell cycle arrest in hTERT RPE1 cells 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite a computational method for the estimation of the gene-dependency level while taking account of the copy-number effect, it is experimentally demanding to determine copy numbers for cell types of interest, while it is still difficult to resolve mismatch-tolerance effect 11,16 . What's more, it has recently been reported that Cas9-induced DSBs posed obstacles to high-throughput screens in human non-transformed cells via p53-dependent cell growth arrest [17][18][19][20] . High-efficiency Cas9 editing could cause cell death in human pluripotent stem cells (hPSCs) 20 and G1 cell cycle arrest in hTERT RPE1 cells 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite a computational method for the estimation of the gene-dependency level while taking account of the copy-number effect, it is experimentally demanding to determine copy numbers for cell types of interest, while it is still difficult to resolve mismatch-tolerance effect 11,16 . What's more, it has recently been reported that Cas9-induced DSBs posed obstacles to high-throughput screens in human non-transformed cells via p53-dependent cell growth arrest [17][18][19][20] . High-efficiency Cas9 editing could cause cell death in human pluripotent stem cells (hPSCs) 20 and G1 cell cycle arrest in hTERT RPE1 cells 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The later study showed that Cas9 toxicity created an obstacle to the highā€throughput use of CRISPR/Cas9 for genome engineering and screening in pluripotent stem cells in response to the Cas9ā€induced break. However, Bowden and coworkers 278 carried out parallel CRISPR/Cas9 screens in wildā€type and knockout hRPECs using a focused dual guide RNA library targeting 852 DNA damage responseā€associated genes. They showed that although functional p53 status negatively affected identification of significantly depleted genes, optimal screen design enabled robust screen performance.…”
Section: Problems and Perspectivesmentioning
confidence: 99%